THE IMPORTANCE OF THE GAME IN THE CREATIVE DEVELOPMENT OF CHILDREN OF PRESCHOOL AGE - Makhbuba B. Jumayeva (Oriental Journal of Education, 2023)
The importance of the game in the creative development of children of preschool age. The importance of play therapy in the activities of preschool children, ways of using game methods in the creative activities of preschool children and mental development of the child